2020
DOI: 10.3847/1538-4357/abbad2
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cosmic Rays on Thermal Instability in the Circumgalactic Medium

Abstract: Large reservoirs of cold (∼10 4 K) gas exist out to and beyond the virial radius in the circumgalactic medium (CGM) of all types of galaxies. Photoionization modeling suggests that cold CGM gas has significantly lower densities than expected by theoretical predictions based on thermal pressure equilibrium with hot CGM gas. In this work, we investigate the impact of cosmic-ray physics on the formation of cold gas via thermal instability. We use idealized three-dimensional magnetohydrodynamic simulations to foll… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
72
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 142 publications
(230 reference statements)
9
72
2
Order By: Relevance
“…In agreement with previous work, the Isolated runs (top row) indicate that including CR permits the presence of low-density, lowtemperature gas, as CR provide nonthermal pressure support (Ji et al 2020;Butsky et al 2020). Note the low temperature ridge at 𝑇 ∼ 10 2 K is weak in NoCR runs (supported only by magnetic pressure in those cases).…”
Section: Gas Phase Distribution In the Disksupporting
confidence: 89%
“…In agreement with previous work, the Isolated runs (top row) indicate that including CR permits the presence of low-density, lowtemperature gas, as CR provide nonthermal pressure support (Ji et al 2020;Butsky et al 2020). Note the low temperature ridge at 𝑇 ∼ 10 2 K is weak in NoCR runs (supported only by magnetic pressure in those cases).…”
Section: Gas Phase Distribution In the Disksupporting
confidence: 89%
“…In contrast, cooler gas in CR+ can remain at intermediate temperatures with volume-filling densities. One might worry that our resolution is insufficient to accurately capture these phenomena (Hummels et al 2019), but recent idealized simulations of the thermal instability in a patch of the CGM with CRs (Butsky et al 2020) have demonstrated exactly the results above, when P cr P thermal .…”
Section: Cooling Efficiency With and Without Dominant Cr Pressurementioning
confidence: 72%
“…Ji, Oh & McCourt 2018;van de Voort et al 2020) and cosmic rays (CRs; e.g. Salem, Bryan & Corlies 2016;Farber et al 2018;Ji et al 2020;Buck et al 2020;Butsky et al 2020), is under increasingly active investigation. Ji et al (2020) utilized FIRE-2 simulations 1 with CR physics incorporated (Chan et al 2019;Hopkins et al 2020c) to investigate the effects of CRs on the CGM properties.…”
mentioning
confidence: 99%
“…11. 11 CR-dominated jets can also help quench by modifying the nonlinear behaviour of the thermal instability, as suggested in Ji et al (2020) and shown rigorously in Butsky et al (2020). In brief: if CR pressure balances gravity and dominates over thermal pressure in a thermally unstable medium, then cooling gas follows total pressure equilibrium (not just thermal pressure equilibrium) and cooling gas can remain diffuse (rather than being compressed to high densities; i.e.…”
Section: Why the Cr Jet Quenches Star Formation More Efficientlymentioning
confidence: 90%